Does the standardisation of tax enforcement improve corporate financial reporting quality? - Xiaojian Tang; Dongying Du; Lina Xie; Bin Lin (China Journal of Accounting Studies (CJAS), 2022)
Previous studies of tax enforcement neglect the effect of tax-penalty discretionary benchmarks on corporate financial reporting quality. In China, province-level variations in implementing tax-penalty discretionary benchmarks provide a quasi-natural experiment to explore how tax enforcement standardisation affects corporate financial reporting quality. We show that when tax-penalty benchmarks are implemented in every province, there is a more pronounced positive relationship between tax enforcement standardisation and corporate financial reporting quality compared with the ex-ante period. Moreover, this positive relationship is primarily driven by firms with higher degrees of tax avoidance and collusion with tax collectors. Consequently, the implementation of tax-penalty benchmarks means that the standardisation of tax enforcement can improve corporate financial reporting quality. In turn, tax enforcement standardisation can optimise the external governance environment for listed firms and improve financial information disclosure in capital markets.
Keywords: 650; Tax-penalty discretionary benchmarks; tax enforcement; standardisation; financial reporting quality; quasi-natural experiment